Calidad de la dieta: Regiones por regiones y departamentos de Guatemala - Ramos Solorzano, Gresia Dalal; Lizarazo Torres, Miguel Angel; Estrada Vargas, Oscar Hernan; Jimenez Rodas, Daniel Ricardo (2025)
The Diet Quality Dashboard for Guatemala provides real-time information on key diet quality indicators derived from participants residing in the eastern, central, and western regions of the country. The dashboard presents results for the Global Diet Quality Score (GDR) and its subcomponents, including NCD-Protect, NCD-Risk, and the All-5 indicator, with data disaggregated by age group and gender. The information displayed covers the period from June 2024 to November 2025 and supports evidence-based decision-making by enabling users to explore patterns and trends in diet quality across regions and population groups. The development and implementation of this dashboard were made possible through the collaboration of local partners, who facilitated engagement with participants and end users. Their involvement was essential to ensuring the relevance of the data for decision-makers and stakeholders at the local and national levels.